The history of press graphics 1819-1921 - Roob, Alexander (TASCHEN, 2023)
"Discover the unique genre of illustrated newspapers and their modernist artistic design. This rich collection explores 100 years of graphic news items and their trailblazing influence on the emerging avant-garde art movements." (Rückseite des hinteren Banddeckels)